Comparative Research on the Game Behavior of the Participants in the Traditional Supply Chain Finance and the Supply Chain Finance on the Blockchain - Yong Luo; Yanhong Tang (Discrete Dynamics in Nature and Society)
The authors took the financing warehouse in supply chain finance as an example, used the game between capital providers (banks and their entrusted logistics supervision enterprises) and capital demanders (core enterprises of supply chain, upstream suppliers, and downstream dealers) as the research object, and constructed the income matrices, respectively, and the Nash equilibrium of pure decision and mixed decision was calculated. The authors compared the game behavior of the participants in the traditional supply chain finance and the supply chain finance on the blockchain and the difference of the mixed decision Nash equilibrium whether blockchain rewards and punishment were added. When the rewards and punishment were added to encourage the transaction information placing in the blockchain, the Nash equilibrium point would be further away from the origin point, and the capital provider and the capital demander would choose to cooperate with greater probability. When the cost of the blockchain is gradually reduced, the two sides of the game choose to place the transaction information in the chain, which can improve the cooperation of the participants of the supply chain finance, and they can get more profit.